Emerging Implications of Blockchain in Global Trade - Madhumita Das; Pravitha Vijaykumar; Habibullah Khan (International Research Journal of Business Studies, 2025)
International trade involves the cross-border exchange of goods and services, reflecting the interconnected flow of commodities and offerings between distinct geographical areas. It is the cornerstone of global business and an important tool for economic interactions between countries. The principle of comparative advantage allows countries to produce and export goods on a global scale that they are more efficient in and import the ones from other nations that they are not. Technical developments have played a significant role in trade evolution. The recent rise of disruptive technologies such as Blockchain has sparked curiosity among stakeholders for its various possible uses in the global trade landscape. Due to its inherent features of security, immutability, and transparency, blockchain technology can significantly enhance trade security, minimize trade costs and eliminate most intermediaries from the trading process. Although Blockchain has the potential to influence international trade significantly, the existing literature has not yet produced any conclusive evidence. This study examines how Blockchain technology affects international trade dynamics. The study also discusses the potential challenges and provides recommendations to enhance Blockchain's impact on world trade, especially for developing nations. Our findings reveal that Blockchain has a prominent role in shaping the future landscape of international trade. However, specific challenges need to be addressed by organizations before reaping the full benefits offered by this innovative technology, which is still in its early stages.